Legal Protection for Directors Related to Agreements with Third Parties that Cause Losses to the Company - Setiawan, Rahmat; Yuhelson, Yuhelson (Jurnal Sosial Teknologi, 2024)
The Board of Directors is obliged to take responsibility for its actions on the employment contract agreement of any responsibility born of any transaction or employment contract activity carried out by it in accordance with the duties and responsibilities given by the board of commissioners to it as a director of the company, with the consideration that the activity has been carried out with due regard to prudential standards and good faith from the duties and functions as a director. The research method used is normative juridical research using primary, secondary, and tertiary legal materials and research places, data collection techniques in this research are literature studies and document studies and interviews, data analysis is carried out by collecting, classifying, and analysing based on the results of literature study research and studies in several companies, the results of the study show that the legal protection of the Board of Directors on agreements with third parties that harm the company so that if something undesirable happens, the sanctions for violations of the Board of Directors in their position as budget users will face criminal, civil and administrative sanctions. So that directors who get authority based on applicable laws and regulations in carrying out a work contract activity either obtained through delegation of authority, then have fulfilled the criteria in each agreement.